Analisis Kebijakan Segmen Pada Perusahaan Asosiasi Serta Kaitannya Dengan PSAK No 5 - Ardhi, Ardhi; Nurjanah, Yayuk (Institut Bisnis dan Informatika Kesatuan, 2014)
The purpose of this research is to analyze segment policies applied by association companies, and investigate if such application is in accordance with PSAK No. 5. Generally companies ' segments are consisted of business and geographical segments. The business segment is divided based into products and services. Mean while, the geographical segment is based on its operating regions. The form of its report is consisted ofsegmented income statement, segmented assets and liabilities, reconciled total revenue, and other material elements between the segment and entities. The result show that most associated companies run their operating segmen based on business and geographic, and not every companies disclose them in accordance with PSAK No. 5. Kata kunci: Business Segment, Geographical Segment, Operating Segment